(untitled) - Olsen, Gregg; Morris, Rebecca T. (New York, NY, 2017)
Investigates the 2009 murder of an Amish wife and mother for which her philandering, technology-using husband and one of his paramours were convicted.
Keywords: Wayne County; Case studies; Wayne County; Ohio; Ohio; Case studies; Murder; Amish; Amish Country (Ohio); History; True crime stories